2017
DOI: 10.5539/ijbm.v12n8p19
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of US Bank Failures during the Financial Crisis

Abstract: Hundreds of banks failed during the financial crisis of 2008 to 2010 causing significant social cost and enfeebling economic growth for years following. In the aftermath of the crisis, regulators responded, as always, with new regulations, the efficacy of which is debatable. For policy makers to enact effective regulation, they must understand the true cause of bank failures during crisis periods. We study the effects of 31 variables using univariate t-tests and probit regression to determine their influence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…This evidence is also consistent with Serrano-Cinca et al (2014) who reported that nonfailed banks compensated for increases in risk by strengthening their core capital. However, Cox et al (2017) found that banks failed during the 2008-2010 financial crisis because they accepted more risk, specifically by having higher financial leverage. This is in line with Serrano-Cinca et al (2014), who showed that 5 years before the crisis, failed banks had higher loan growths, higher concentration on real estate loans, higher risk ratios, and higher turnover, but lower margins.…”
Section: Discussion and Managerial Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This evidence is also consistent with Serrano-Cinca et al (2014) who reported that nonfailed banks compensated for increases in risk by strengthening their core capital. However, Cox et al (2017) found that banks failed during the 2008-2010 financial crisis because they accepted more risk, specifically by having higher financial leverage. This is in line with Serrano-Cinca et al (2014), who showed that 5 years before the crisis, failed banks had higher loan growths, higher concentration on real estate loans, higher risk ratios, and higher turnover, but lower margins.…”
Section: Discussion and Managerial Implicationsmentioning
confidence: 99%
“…Although an unprecedented number of banks collapsed or were bailed out by governments during the crisis (Erkens et al, 2012), not all banks across the world performed equally poorly; some banks performed better during the crisis (Beltratti & Stulz, 2012). To explore this phenomenon, several papers such as Beltratti and Stulz (2012), Serrano-Cinca et al (2014), Adebambo et al (2015), Cox et al (2017), and Avkiran et al (2018) investigated the impact of financial crisis on banks' performance from a variety of perspectives. Thus far, however, insufficient attention has been paid by these studies to the role of prioritization of managerial decisions and policy activities in precipitating the financial crisis.…”
Section: Introductionmentioning
confidence: 99%
“…al., (2007), after providing a thorough literature review related to firms' and financial institutions' bankruptcies from 1930 to 2007, deduce that "some models with two factors are just as capable of accurate prediction as models with 21 factors. " Cox et. al., (2017) conducted that the cause of US bank failures during the recent financial crisis was poor management.…”
Section: Bank Failuresmentioning
confidence: 99%